A dinâmica territorial da Assembléia de Deus no Seridó do Rio Grande do Norte - Araujo, Bruno Gomes de (2010)
In the norte-rio-grandense backwoods is possible to join to the power forms both political and economical ones, religious groups keeping under your control areas, people and flow of them, as well as settling new places of acts. That control refers to a field of power delimited by space, in other words, it refers to a territory marked and planned to reproductive intentions on the space. In relation to the religious pluralism, the Assembly of God church, in your territorial dynamics, has been standing out by the strategies of delimitation and space increase which by a constant territorial division process (1943-2010) managed to widen material and symbolic scale of its power for all cities of the Rio Grande do Norte backwoods. The Assembly of God church as the greatest Pentecostal denomination of Brazil was formed in the Rio Grande do Norte Seridó, following a ecclesiastical and governmental model divided into three ecclesiastical fields hosted in those following cities: Caicó, Currais Novos and Parelhas. Those headquarters interlink a limited number of churches through normative codes, which they express a functional dimension (bureaucratic) and in another symbolic one (charismatic) in an only field of territorial control. In this manner, the maintenance of the territorial power in the Assembly of God church is done by a charismatic-bureaucratic administration, expressed in the interdependent of material and abstract mechanisms. The believers permanent contact toward those mechanisms of institutional control revealed territorial identities which causes a feeling of property of the believer as much to the Pentecostal belief system as to community of the Assembly of God church. Considering new possibilities of articulation of the Rio Grande do Norte backwoods towards others territories more multiple, culturally, noticed cultural adjustments and revaluation at themselves. In relation to the territory of the Assembly of God church this one has exposed itself defensive faced with that cultural hybridization tendency, resisting a closer dialogue to new symbolic elements, mainly those came from the multifaceted neo-pentecostal movement. Unlike more open and flexible churches towards others significant systems, The Assembly of God church tries to reinforce the boundaries of its territory considering by the orthodoxy of its routine and customs